Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

If the sum of the first 10 terms of an arithmetic series is 27.5 and the [tex]$10^{\text{th}}$[/tex] term of the series is 5, determine the value of the first term and the common difference.

Sagot :

Certainly! Let's work through this problem step-by-step. We need to find the first term ([tex]\(a\)[/tex]) and the common difference ([tex]\(d\)[/tex]) of an arithmetic series given the sum of the first 10 terms ([tex]\(S_{10} = 27.5\)[/tex]) and the 10th term ([tex]\(a_{10} = 5\)[/tex]).

### Step 1: Use the formula for the nth term of an arithmetic series
The general formula for the [tex]\(n\)[/tex]th term ([tex]\(a_n\)[/tex]) of an arithmetic series is:
[tex]\[ a_n = a + (n-1)d \][/tex]

For the 10th term:
[tex]\[ a_{10} = a + 9d \][/tex]
Given [tex]\(a_{10} = 5\)[/tex]:
[tex]\[ 5 = a + 9d \][/tex]
Rearrange to solve for [tex]\(a\)[/tex]:
[tex]\[ a = 5 - 9d \quad \text{(Equation 1)} \][/tex]

### Step 2: Use the formula for the sum of the first [tex]\(n\)[/tex] terms of an arithmetic series
The formula for the sum of the first [tex]\(n\)[/tex] terms ([tex]\(S_n\)[/tex]) is:
[tex]\[ S_n = \frac{n}{2} \left( 2a + (n-1)d \right) \][/tex]

For the sum of the first 10 terms:
[tex]\[ S_{10} = \frac{10}{2} \left( 2a + 9d \right) \][/tex]
Given [tex]\(S_{10} = 27.5\)[/tex]:
[tex]\[ 27.5 = 5 \left( 2a + 9d \right) \][/tex]
Simplify:
[tex]\[ 5.5 = 2a + 9d \quad \text{(Equation 2)} \][/tex]

### Step 3: Substitute Equation 1 into Equation 2
Substitute [tex]\(a = 5 - 9d\)[/tex] from Equation 1 into Equation 2:
[tex]\[ 5.5 = 2(5 - 9d) + 9d \][/tex]
Expand and simplify:
[tex]\[ 5.5 = 10 - 18d + 9d \][/tex]
[tex]\[ 5.5 = 10 - 9d \][/tex]
Rearrange to solve for [tex]\(d\)[/tex]:
[tex]\[ -4.5 = -9d \][/tex]
[tex]\[ d = 0.5 \][/tex]

### Step 4: Substitute [tex]\(d\)[/tex] back into Equation 1 to find [tex]\(a\)[/tex]
Now, substitute [tex]\(d = 0.5\)[/tex] back into Equation 1:
[tex]\[ a = 5 - 9(0.5) \][/tex]
[tex]\[ a = 5 - 4.5 \][/tex]
[tex]\[ a = 0.5 \][/tex]

### Summary
The first term [tex]\(a\)[/tex] is [tex]\(0.5\)[/tex], and the common difference [tex]\(d\)[/tex] is [tex]\(0.5\)[/tex].